Advances in Biomarker-Guided Therapy for Pediatric- and Adult-Onset Neuroinflammatory Disorders: Targeting Chemokines/Cytokines - Pranzatelli, Michael R. (Frontiers in Immunology, 2018)
The concept and recognized components of “neuroinflammation” are expanding at the intersection of neurobiology and immunobiology. Chemokines, no longer merely necessary for immune cell trafficking and positioning, have multiple physiologic, developmental, and modulatory functionalities in the CNS through neuron-glia interactions and other mechanisms affecting neurotransmission. They issue the “help me” cry of neurons and astrocytes in response to CNS injury, engaging invading lymphoid cells (T cells, B cells) and myeloid cells (dendritic cells, monocytes, neutrophils) (adaptive immunity), as well as microglia and macrophages (innate immunity), in a cascade of events, some beneficial (reparative), others destructive (excitotoxic). Human CSF studies have been instrumental in revealing soluble immuno-biomarkers involved in immune dysregulation, their dichotomous effects, and the cells—often subtype-specific—that produce them. Chemokines/cytokines continue to be attractive targets for the pharmaceutical industry with varying therapeutic success. This review summarizes the developing armamentarium, complexities of not compromising surveillance/physiologic functions, and insights on applicable strategies for neuroinflammatory disorders. The main approach has been using a designer monoclonal antibody to bind directly to the chemo/cytokine. Another approach is soluble receptors to bind the chemo/cytokine molecule (receptor ligand). Recombinant fusion proteins combine a key component of the receptor with IgG1. An additional approach is small molecule antagonists (protein therapeutics, binding proteins, protein antagonists). Chemokine neutralizing molecules (“neutraligands”) that are not receptor antagonists, high affinity neuroligands (“decoy molecules”), as well as neutralizing “nanobodies” (single domain camelid antibody fragment) are being developed. Simultaneous, more precise targeting of more than one cytokine is possible using bispecific agents (fusion antibodies). It is also possible to inhibit part of a signaling cascade to spare protective cytokine effects. “Fusokines” (fusion of two cytokines or a cytokine and chemokine) allow greater synergistic bioactivity than individual cytokines. Another promising approach is experimental targeting of the NLRP3 inflammasome, amply expressed in the CNS and a key contributor to neuroinflammation. Serendipitous discovery is not to be discounted. Filling in knowledge gaps between pediatric- and adult-onset neuroinflammation by systematic collection of CSF data on chemokines/cytokines in temporal and clinical contexts and incorporating immuno-biomarkers in clinical trials is a challenge hereby set forth for clinicians and researchers.